Surveilans Dinamis Polutan Laut dan Upaya Pencegahan Penyakit Berbasis Lingkungan Melalui Pengabdian di Pulau Tidung - Agung Kwartama; Samiyono; Anton Novianto; Paiman; Indah Sulita; Abdul Rasyid; Gatot Prasojo; Hidayat Kurahmadan; Nor Fauziah; Yanto Rusmanto; Bangun Husodo; Akhmad Sopani; Didik Indriawan; Sumiyatiningsih; Lie Adek; Desiana Endah Pramesti; Ramayanti; Syafril Zulmaidi; Dwi Wuryani; Deferiansyah; Abdul Aziz (Lembaga Pengembangan Kinerja Dosen, 2025)
Tidung Island, located in the Seribu Islands, faces serious challenges in maintaining environmental health due to increasing marine pollution. This pollution primarily originates from domestic waste, uncontrolled tourism activities, and the accumulation of hazardous pollutants such as heavy metals and microplastics. These conditions directly and indirectly increase the risk of environmentally-based health problems in coastal communities, such as skin diseases, respiratory disorders, and potential poisoning from exposure to hazardous chemicals. This situation is further exacerbated by the absence of an integrated and participatory environmental surveillance system, resulting in weak early detection of pollutant exposure and community response capabilities. This research was conducted using a descriptive qualitative approach through in-depth interviews, field observations, and documentation studies to obtain a comprehensive picture of the relationship between environmental pollution and public health. The research analysis utilized health ecology theory, which emphasizes the close relationship between physical environmental conditions, human behavior, and their impacts on community health. The results indicate that community involvement in environmental quality monitoring and health education is key to strengthening the community-based surveillance system. Thus, the community plays a role not only as a recipient of information but also as an active actor in maintaining environmental sustainability. This approach is expected to increase collective awareness and accelerate mitigation actions against health risks caused by pollution. The study's conclusions emphasize the importance of developing participatory surveillance systems that adapt to local contexts, particularly in island regions with limited infrastructure access. Further research recommends quantitative measurements of the biomedical impacts of pollutants, as well as the use of digital technology to develop more modern, efficient, and sustainable environmental monitoring systems.